(untitled) (Research, Society and Development, 2025)
Transthyretin Amyloidosis is a type of amyloidosis that is both hereditary and acquired, and results in the deposition of amyloid fibrils in different tissues. Therefore, it affects multiple organs and can lead to cardiomyopathy, dysautonomia, diastolic heart failure with preserved ejection fraction, and peripheral polyneuropathy, affecting the individual’s quality of life, autonomy, and dependence for basic daily activities, in addition to increasing the rate of comorbidities and chronic complications and reducing the patient’s life expectancy. Although it is a rare pathology, given its severity and long-term damage, new drugs for treatment are produced and studied every year through the adoption of innovative technologies. In the last 15 years, drug classes have been improved, such as Transthyretin stabilizers, gene silencers, anti-inflammatories, and symptomatic agents. The objective of this article is to summarize the updates on the treatment and therapies that modify the course of Transthyretin Amyloidosis, and to help in the understanding of the subject as well as to identify gaps that require further research. The study methodology corresponds to a Narrative Review composed of studies published in the last 15 years, from Journals recognized for their high scientific quality and contribution to advances in health. Priority was given to the pyramid of scientific evidence, with meta-analyses, systematic reviews, intervention studies such as randomized clinical trials, open trials and dose-dependent, cohort and case-control trials, and then critically discussing the results found.